Emerging Opportunities for "Design Thinking" to Deliver Sustainable Solutions in the Built Environment - Wilson, K.; Desha, C.; Bucolo, S.; Miller, E.; Hargroves, Charlie (Common Ground Publishing, 2014)
In the built environment sector, a range of innovations are delivering environmental improvements with mixed success worldwide. The authors of this paper argue that a more “disruptive” form of innovation is needed to bring about significant and systemic change within the sector. Critical to this transition is the development of new behaviours and values. In particular, built environment professionals need to become active change agents in cultivating these new behaviours and values through the development of collaborative visions, scenarios, practices, and ideas. This paper identifies and discusses the critical role that design (in its broadest sense) can play in this process. Drawing on a comprehensive review of literature, the authors highlight a number of transformational opportunities for cross-professional learning and sharing between design and built environment disciplines in achieving environmental innovation (eco-innovation). The paper also considers several design-based concepts that have a potential application in the built environment sector including: design thinking, social innovation (human-centered), and disruptive innovation (transformational) approaches. The research findings will assist in building the capabilities of designers and innovators to create sustainable solutions to global problems, and in supporting the social diffusion of systems-changing ideas in the built environment sector.